2002
DOI: 10.1159/000064694
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Reproducibility of Ultrasound Measurements in Obstetric Management

Abstract: Objective: The aim of this study was to assess the potential of ultrasonography as a routine diagnostic tool in obstetric management. Subjects and Methods: For the investigation on interobserver reproducibility, 2 sonologists independently measured the biparietal diameter (BPD), femur length (FL), amniotic fluid index (AFI), and resistance index (RI) of the umbilical and middle cerebral arteries in 20 healthy pregnant women between 28 and 36 weeks of gestation using color and pulsed Doppler ultrasound. A secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Intraobserver and interobserver variability of sonographic measurements varies widely, according to the sonographic measurement studied. Reliability measurements for the AFV show only moderate interobserver and intraobserver correlations, 7,8 whereas fetal biometric measurements are highly reproducible. 7,9,10 Reliability measurements of the fetal circulation vary by report and vessel studied.…”
Section: Discussionmentioning
confidence: 93%
“…Intraobserver and interobserver variability of sonographic measurements varies widely, according to the sonographic measurement studied. Reliability measurements for the AFV show only moderate interobserver and intraobserver correlations, 7,8 whereas fetal biometric measurements are highly reproducible. 7,9,10 Reliability measurements of the fetal circulation vary by report and vessel studied.…”
Section: Discussionmentioning
confidence: 93%
“…In the light of these publications. it can be said that coloured Doppler application is widely used in the evaluation of fetal well-being while it has also become important in reducing the perinatal mortality and morbidity rates especially in high-risk pregnancies (12)(13)(14)(15). Coloured Doppler application is able to provide information about the early diagnosis of fetal distress quicker than other tests and this is its main advantage (12).…”
Section: Methodsmentioning
confidence: 99%
“…This trend is known to be more pronounced for HC and AC than for FL [18]. However, studies have also shown good intraand inter observer reproducibility of ultrasound measurements of fetal biometry [25][26][27]. In the INTERGROWTH21st study centiles were derived from serial (longitudinal) measurements from each fetus [19].…”
Section: Papermentioning
confidence: 99%